2019
DOI: 10.1038/s41598-018-36907-x
|View full text |Cite
|
Sign up to set email alerts
|

Plant microbiome-dependent immune enhancing action of Echinacea purpurea is enhanced by soil organic matter content

Abstract: We previously demonstrated that extracts from Echinacea purpurea material varied substantially in their ability to activate macrophages in vitro and that this variation was due to differences in their content of bacterial components. The purpose of the current study was to identify soil conditions (organic matter, nitrogen, and moisture content) that alter the macrophage activation potential of E. purpurea and determine whether these changes in activity correspond to shifts in the plant-associated microbiome. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Sugarcanesoybean intercropping increased microbial diversity [29]. Microbiome-dependent immunity was related to soil organic matter content [30]. It was reported in previous studies that intercropping can change the soil microecology, as indicated by increasing farmland biodiversity [31].…”
Section: Introductionmentioning
confidence: 83%
“…Sugarcanesoybean intercropping increased microbial diversity [29]. Microbiome-dependent immunity was related to soil organic matter content [30]. It was reported in previous studies that intercropping can change the soil microecology, as indicated by increasing farmland biodiversity [31].…”
Section: Introductionmentioning
confidence: 83%
“…Thus, beside the potential impact of the plant microbiome on pathogen resistance and general fitness evidence has accumulated that the microbiome has a significant impact on the production of secondary metabolites of MPs ( Köberl et al, 2013 ; Schmidt et al, 2014 ; Jia et al, 2016 ; Huang et al, 2018 ; Pacifico et al, 2019 ). This has recently been specified for Echinacea purpurea ( Maggini et al, 2017 ; Haron et al, 2019 ), Camellia sinensis ( Sun et al, 2019 ), and Cannabis sativa ( Taghinasab and Jabaji, 2020 ). Further work is still required to illuminate mutual interactions of MPs and their microbiome and its potential role in producing beneficial bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies also relevant that echinacoside and caffeic acid derivative have weak anti-bacterial and antiviral effects and are protectants against reactive oxygen species 20,39 . The antioxidant activity could be ascribed to the polyphenolic components 13 , such as flavonoids 34 , phenolic acids 35 or phenolic diterpenes 9 .…”
Section: Discussionmentioning
confidence: 99%
“…It is resistance to heat or cold weather conditions, easy to grow, and flaunt high efficiency 7 , 8 . Numerous scientific researches demonstrated the useful effect of Echinacea immunomodulatory functions and human health 9 , 10 . The doctors explored that the alcohol extract of Echinacea rhizomata cum radicibus immediately increased phagocytic activity and leads to high production of white blood cells, as well as, various in vitro researches has confirmed the phagocytosis, and antibody-dependent cellular cytotoxicity effects of E. purpurea rhizomata cum radicibus extracts 4 .…”
Section: Introductionmentioning
confidence: 99%